Analisis Yuridis Kompensasi pada Peraturan Pemerintah Nomor 35 Tahun 2021 Tentang Perjanjian Kerja Waktu Tertentu, Alih Daya (Outsourcing), Waktu/Jam Kerja dan Waktu Istirahat, dan Pemutusan Hubungan Kerja - Toha, Imam Sofii; Rahmatiar, Yuniar; Abas, Muhamad; Amaliya, Lia (Universitas Batanghari Jambi, 2023)
The motivation behind this composing is to specify the execution of Article 64 of Unofficial law (PP) Number 35 of 2021 Concerning Explicit Time Work Arrangements, Reevaluating, Working Time/Hours and Rest, and End of Business, as well as methodology for execution in light of Unofficial law 35 of 2021 concerning Time Arrangements. Explicitly re-appropriating, working time/hours and rest periods, as well as end of business connected with Unofficial law in Lieu of Regulation (Perppu) Number 2 of 2022 concerning Position Creation. In this review, the creators utilize a standardizing juridical methodology as a technique for approach. The end is that Administration Guideline (PP) Number 35 of 2021 concerning Work Arrangements for Explicit Periods, Re-appropriating, Working Hours and Breaks, and End of Business, which corrects Regulation Number 13 of 2003 concerning Labor makes regulations for laborers. The legitimate outcome is that the temporary guidelines are not directed, which makes managers randomly utilize laborers with PKWT status for over 5 years with no juridical results.